Queirolo, Graciela (2018). Mujeres en las oficinas. Trabajo, género y clase en el sector administrativo (Buenos Aires, 1910-1950). Buenos Aires: Biblos. 270 páginas. ISBN 978-987-691-669-1 - Garazi, Débora (2019)
Reseña de Queirolo, Graciela (2018), Mujeres en las oficinas. Trabajo, género y clase en el sector administrativo (Buenos Aires, 1910-1950). Buenos Aires: Biblos. 270 páginas. ISBN 978-987-691-669-1